Cp*CoIII-Catalyzed C–H Functionalization and Asymmetric Reactions Using External Chiral Sources - Yoshino, Tatsuhiko; Matsunaga, Shigeki (Synlett, 2019)
This account describes Cp*CoIII-catalyzed C–H functionalization reactions developed in our group between 2013 and 2018. Cp*CoIII catalysts not only serve as inexpensive alternatives to Cp*RhIII catalysts but also exhibit unique reactivity and selectivity in several transformations. In the latter part of this review, we introduce catalytic asymmetric C–H functionalization reactions using achiral RhIII or CoIII catalysts with chiral disulfonates or carboxylic acids as external chiral sources.1 Introduction and Overview2 Cp*CoIII-Catalyzed C–H Functionalization Reactions2.1 C–H Addition Reactions to Polar Double Bonds2.2 Cp*Co(CO)I2 and [Cp*CoI2]2 Precursors for the C2-selective C–H Amidation of Indoles2.3 C–H Functionalization of Carbamoyl-Protected Indoles Using Alkynes2.4 C–H Allylation Using Allyl Alcohols2.5 Cyclization Reactions of O-Acyloximes and Alkynes2.6 Other Miscellaneous Reactions3 Enantioselective C–H Functionalization Reactions by Hybrid Catalysis3.1 Cp*RhIII/Chiral Disulfonate Catalysts for the Enantioselective C–H Addition to Enones3.2 Enantioselective C–H Cleavage Using Chiral Carboxylic Acids4 Summary and Perspective
Keywords: C–H functionalization; C–H activation; cobalt; rhodium; asymmetric catalysis